Environmental Changes of the Temirnik River in Rostov-on-Don: Perubahan Lingkungan Sungai Temirnik di Rostov-on-Don - Murooj Abbas Buhlool AL-Ghizzi; Zahraa Zahraw Al-Janabi (Academia Open, 2024)
General Background: The increasing anthropogenic impact on river ecosystems has raised concerns about water quality and its effects on surrounding communities. Specific Background: This study focuses on the Temirnik River, located in the northern part of the city, particularly assessing pollution levels in the beaches of "Druzhba" and "Surp Khash." Historical data from 2000-2001 and recent analyses from 2017-2019 reveal significant fluctuations in chemical and biological toxicity. Knowledge Gap: While previous studies have documented pollution levels, a comprehensive comparison of historical and recent data to understand long-term changes and community impacts remains insufficiently explored. Aims: This study aims to track changes in pollution levels over time, evaluate the chemical and biological toxicity, and assess the anthropogenic impacts on the Temirnik River. Results: Chemical analysis revealed increased hardness of water due to the accumulation of calcium and magnesium sulfates and chlorides. The river, heavily impacted by untreated industrial and municipal waste, showed high toxicity levels, especially in the years 2017-2019. Bioassays using Chlorella vulgaris, Raphanus sativus, and Daphnia magna confirmed these findings. Novelty: This study provides a detailed comparative analysis of historical and contemporary pollution data, highlighting the persistent and worsening impact of anthropogenic activities on the Temirnik River. Implications: The findings underscore the critical need for ongoing monitoring and intervention to mitigate pollution. They advocate for implementing effective cleaning operations and regulatory measures to protect water quality and community health. Highlights: Increased water hardness from industrial and municipal waste. Persistent high toxicity levels impacting ecosystems. Urgent need for continuous monitoring and pollution control. Keywords: Temirnik River, chemical pollution, biological toxicity, historical data, anthropogenic impact